Analysis of Stock Prices and Stock Trading Volumes Before and After Unusual Market Activity (UMA) on the Indonesia Stock Exchange (IDX) in 2019 - Dedy Dwi Arseto (The Indonesia Capital Market Institute, 2021)
Analysis of Stock Prices and Stock Trading Volumes Before and After Unusual Market Activity (UMA) on the Indonesia Stock Exchange (IDX) in 2019. This study aims to determine the difference in stock prices and stock trading volumes before and after the announcement of Unusual Market Activity (UMA) on the Stock Exchange. The Indonesian Stock Exchange (IDX) in 2019. The population in this study amounted to 84 issuers with a sample of 20 issuers. Sampling using Non Probality Sampling, with the sampling technique is Purposive Sampling. Research data collection techniques using observational data and literature study. The data analysis technique used descriptive statistical analysis, the Shapiro-Wilk normality test, the Wilcoxon signed rank test hypothesis. The results showed that there was no difference in stock prices in stocks before and after the announcement of Unusual Market Activity (UMA) on the Indonesia Stock Exchange (IDX) in 2019 and there were differences in stock trading volume in stocks before and after the announcement of Unusual Market Activity (UMA) on the Stock Exchange. Indonesia (IDX) in 2019..